AKSI UNJUK RASA (DAN RADIKALISME) SERTA PENANGANANNYA DALAM ALAM ”DEMOKRASI” DI INDONESIA (Forum Penelitian Agro Ekonomi, 2016)
Currently, almost every single ‘conflict’ in the society is followed by demonstration.  It seems that the demonstration is a popular trend after the New Order era and more specifically such fenomenon has been reflected in the modern democracy life of the society.  Understanding about democracy is heavily depending on the eliteness maturity of someone (politic, economy, and government). In the present ‘transitional situation’ and the absence of the ideal socio-culture-politic level, understanding about democracy will invite pros and cons among the concerned people. To express disagreement on certain public policies through demonstration could be accepted because it is in lione with “democracy”. However, such protest along with anarchy actions and radicalism should create undesirable situation.affecting the public. Traditionally, protest (by the people) which is responded wisely (by the government) has been long time exist within the old society (such as Java’s kingdom in the past, 16-19 century), long before the “westernization” of Indonesian community. Coping with demonstration is no less than good attitude responses, and far from enemy impression.  Good communication and compromise based on respectful between the two sides will open an elegant solution and parallel with the constitution objectives.
Keywords: demonstration; democracy; public room; corruption; radicalism; aksi unjuk rasa; demokrasi; ruang publik; korupsi; radikalisme